The Deleterious Effects of COVID-19 in the Peripartum Period: A Case Report - Alixandria F. Pfeiffer; Rosylyn James; Barbara K. Neuhoff; Wilson B. Pfeiffer; David R. Lowery; Syed A. A. Rizvi (MDPI AG, 2021)
While the Coronavirus Disease 2019 (COVID-19) pandemic continues to wreak havoc across the nation and the globe as one of the most significant global health crises of our time, recent attention has been turned to the effects of COVID-19 on pregnancy and the puerperium. Although most cases have been asymptomatic, for some patients, the disease may be accompanied by serious complications such as pneumonia, acute respiratory distress, multi organ failure, and death. Several case studies have noted that patients with co-morbidities are at a significant risk of these complications. In a recent systematic review and meta-analysis, authors conclude that cardiovascular disease was associated with increased composite poor outcome in patients with COVID-19. The following case report highlights the multi-system complications and severity of symptoms that can take place after childbirth in a patient with co-morbid obstetric and prenatal conditions and an initially asymptomatic COVID-19 infection.